Pengaruh Current Ratio, Debt to Equity Ratio, Inventory Turnover dan Return on Equity Terhadap Price Earning Ratio - Thio Kori Karunia Odelia; Bonifatius Junianto Wibowo (JEMAP, 2019)
This research was conducted to examine the effect of Current Ratio, Debt to Equity Ratio, Inventory Turnover and Return on Equity on Price Earning Ratio at the automotive industries in Indonesia.  The samples of this research were 12 automotive industry companies which go public.  The data of  this research   was secondary data, which obtained from financial statement of 12 automotive industry companies.  Those data was collected from www.idx.co.id.  Then, The data was analysed by multiple linear regression techniques with the t test. The result shows that the Current Ratio, Debt to Equity Ratio, Inventory Turnover and Return on Equity variables have no effect on Price Earning Ratio.  It means that Price Earning Ratio is not determined by Current Ratio, Debt to Equity Ratio, Inventory Turnover and Return on Equity, but by other factors such as business costs, economic and monetary conditions.